1998
DOI: 10.1088/0967-3334/19/1/003
|View full text |Cite
|
Sign up to set email alerts
|

Influences of lung parenchyma density and thoracic fluid on ventilatory EIT measurements

Abstract: Ventilatory impedance changes can be measured by electrical impedance tomography (EIT). Several studies have pointed out that the ventilatory-induced impedance change measured over the lungs shows a linear relationship with tidal volume. However, EIT measures the ventilatory impedance changes relative to a reference. Therefore, changes in the reference due to lung parenchyma destruction (increase of thoracic impedance) or lung water (decrease of thoracic impedance) might influence ventilatory EIT measurements.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 16 publications
1
14
0
1
Order By: Relevance
“…The lower VIC in the nondependent part of the lung is influenced by the decrease in lung volume due to an increase in the severity of ARF. 7,10 In our study, a significantly higher LIS was found in the group at high PEEP levels, indicating the increase in severity of ARF. The significant increase in IR at higher PEEP levels suggests an increase of Vt in the dependent part of the lung, and thus alveolar recruitment at higher levels of PEEP.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The lower VIC in the nondependent part of the lung is influenced by the decrease in lung volume due to an increase in the severity of ARF. 7,10 In our study, a significantly higher LIS was found in the group at high PEEP levels, indicating the increase in severity of ARF. The significant increase in IR at higher PEEP levels suggests an increase of Vt in the dependent part of the lung, and thus alveolar recruitment at higher levels of PEEP.…”
Section: Discussionsupporting
confidence: 54%
“…However, VIC is not solely determined by the Vt, but also by the amount of lung parenchyma and lung edema. 7 Therefore, in the second part of the study, intraindividual PEEPinduced changes were measured by EIT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in previous studies, effects of acute lung injury, bronchial carcinoma, lung oedema, emphysema, etc. can be identified 6,25,39–41 . Moreover, the effects of artificial ventilation can be assessed and the functional response of lung tissue to various ventilator settings determined 7,9,15,23,25,27,30 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, on measuring changes in ventilation, we may be overlapping intrathoracic fluid changes (pleural effusion, pulmonary extravascular water, pulmonary blood volume), which likewise can cause variations in the impedance results. 62 It is therefore essential to associate the changes visualized by the system with the clinical changes of the patient (a circumstance not exclusive of EIT), in order to ensure their correct interpretation.…”
Section: Limitations Of the Techniquementioning
confidence: 99%